5PSQ-028 Assessment of suspicion of allergy to coronavirus disease 2019 vaccine by skin testing: results from a monocentric cohort. (23rd March 2022) - Lafci, G; Cuvillon, E; Pelletier de Chambure, D; Odou, P; Lannoy, D; Chenivesse, C
Abstract : Background and importance: National recommendations mention vaccinating against COVID-19 patients at risk of allergy after referring them to an allergologist. Included patients had suspected allergy to one of the vaccine's components (polyethylene glycols (PEG) and polysorbates) or with a history of immediate reaction to a first injection of an mRNA vaccine. Patients at risk were referred to the allergology unit for investigation. Aim and objectives: The purpose of this monocentric retrospective study was to assess positive skin tests (ST), and anaphylaxis reaction during vaccination after allergological work-up. Material and methods: For any tested patient, pharmacy extemporaneously prepared: PEG 400 and 4000 (100 mg/mL), prick 1:1 and intradermal tests (IDT) 1:100 000, 1:10 000, 1:1000, 1:100, 1:10; polysorbate 80 (PS80) (0.4 mg/mL), prick 1:1, IDT 1:1000, 1:100, 1:10; and Comirnaty vaccine (30 µg/0.3 mL), prick 1:1 and IDT 1:10. ST readings were done after 20 minutes. Patients' characteristics, test results and indications of allergological work-up were collected. Vaccination was authorised if negative ST. Patients were systematically recalled after vaccination to assess side effects including anaphylaxis. Results: Between 1 February and 31 August 2021, 49 patients, age (mean±SD) 54.5±17.8 years and female 81.6%, performed ST: 20 were tested after a reaction to the Comirnaty (19 after the first dose and 1 after the second dose) and 29 for a suspected allergy to an excipient. Among them, 3 had positive ST (one patient to PS80 prick test and vaccine IDT 1:10, and two patients to vaccine IDT 1:10 without positive ST to PS80 and PEG). Vaccination with Cominarty was contraindicated for these 3 patients. Four patients had delayed positive ST to the vaccine. They were not considered allergic and vaccination was authorised. Of the 46 patients with negative ST, 39 (85%) were vaccinated (one with VaxZveria) without any anaphylaxis reaction (7 did not answer the pharmacist's call). Conclusion and relevance: Positive ST to the vaccine are rare (6%). No patients had simultaneously positive ST to the vaccine and PEG. These results may suggest that the exact predictive positive value remain uncertain and that IDT to the vaccine might be irritating. References and/or acknowledgements: Conflict of interest: No conflict of interest